2016
DOI: 10.1016/j.celrep.2016.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Stalled DNA Replication Forks at the Endogenous GAA Repeats Drive Repeat Expansion in Friedreich’s Ataxia Cells

Abstract: SUMMARY Friedreich's ataxia (FRDA) is caused by the expansion of GAA repeats located in the Frataxin (FXN) gene. The GAA repeats continue to expand in FRDA patients, aggravating symptoms and contributing to disease progression. The mechanism leading to repeats expansion and decreased FXN transcription remains unclear. Using single molecule analysis of replicated DNA, we detected that expanded GAA repeats present a substantial obstacle for the replication machinery at the FXN locus in FRDA cells. Furthermore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 39 publications
7
60
0
Order By: Relevance
“…The alternative mechanisms that promote repeat instability and that are involved in the processing of unconventional DNA structures include incorrect recruitment of mismatch repair proteins and activation of the base excision repair pathway (Du et al 2012;Gannon et al 2012;Halabi et al 2012;Lokanga et al 2014Lokanga et al , 2015Zhao et al 2015). Other potential mechanisms for repeat instability which rely on DNA replication include DNA polymerase stalling and fork collapse, which result in error-prone repair, and DNA polymerase strand-slippage during DNA synthesis (Usdin and Woodford 1995;Voineagu et al 2009;Gerhardt et al 2014Gerhardt et al , 2016Kononenko et al 2018). Regardless of whether the mechanism is repair or replication, our results are consistent with earlier studies on the induction of ssDNA displacements by long microsatellite repeat tracts (Pearson and Sinden 1996;Pearson et al 1998bPearson et al , 2002Tam et al 2003;Panigrahi et al 2005Panigrahi et al , 2010Axford et al 2013;Slean et al 2013Slean et al , 2016Kononenko et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The alternative mechanisms that promote repeat instability and that are involved in the processing of unconventional DNA structures include incorrect recruitment of mismatch repair proteins and activation of the base excision repair pathway (Du et al 2012;Gannon et al 2012;Halabi et al 2012;Lokanga et al 2014Lokanga et al , 2015Zhao et al 2015). Other potential mechanisms for repeat instability which rely on DNA replication include DNA polymerase stalling and fork collapse, which result in error-prone repair, and DNA polymerase strand-slippage during DNA synthesis (Usdin and Woodford 1995;Voineagu et al 2009;Gerhardt et al 2014Gerhardt et al , 2016Kononenko et al 2018). Regardless of whether the mechanism is repair or replication, our results are consistent with earlier studies on the induction of ssDNA displacements by long microsatellite repeat tracts (Pearson and Sinden 1996;Pearson et al 1998bPearson et al , 2002Tam et al 2003;Panigrahi et al 2005Panigrahi et al , 2010Axford et al 2013;Slean et al 2013Slean et al , 2016Kononenko et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a long tract of polypurine-polypyrimidine (GAA) n repeats (in which n can exceed 1,500) is linked to the inherited neurodegenerative disorder Friedreich's ataxia (Campuzano et al, 1996). These repeats can form H-DNA (Frank-Kamenetskii & Mirkin, 1995), a triplex DNA structure able to block replication both in bacterial, yeast and human cells (Ohshima et al, 1998;Krasilnikova & Mirkin, 2004;Chandok et al, 2012), which can promote genetic instability of the repeat (Gerhardt et al, 2016). Furthermore, these repetitive tracts are prone to form R-loops (Groh et al, 2014), three-stranded nucleic acid structures in which nascent RNA hybridises to its complementary DNA template, displacing the non-template DNA strand (Thomas et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…16 It was observed that women with a PM and at least one AGG interruption within the CGG repeat sequence are less likely to have an expansion of CGG repeat length into a FM and consequently are less likely to have a child with FXS in the next generation. [17][18][19] This could potentially be explained by inhibition of the formation of secondary structures at the DNA level, which in turn would diminish the chance of DNA polymerase stalling and slippage, [20][21][22] otherwise responsible for repeat expansions. It has also been shown that RNA containing the FMR1 CGG repeats is also able to form secondary hairpin structures in vitro.…”
Section: Introductionmentioning
confidence: 99%